THE FEATURES OF FORMING OF THE PATHOLOGY OF PERIODONTAL TISSUES IN CHILDREN LIVING IN ECOLOGICALLY UNFAVORABLE TERRITORY - N.V. Malko; E.V. Bezvushko (Український стоматологічний альманах, 2018)
The last year of studies indicate on the high prevalence of main dental diseases in children from ecologically unfavorable regions. Periodontal diseases take the second place by frequency and prevalence after caries, therefore is the significant problem of the pediatric dentistry.